2013
DOI: 10.1371/journal.pone.0056178
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Impressions Do Not Mirror Online Reading Effort: Concurrent EEG-Eyetracking Evidence from the Reading of Books and Digital Media

Abstract: In the rapidly changing circumstances of our increasingly digital world, reading is also becoming an increasingly digital experience: electronic books (e-books) are now outselling print books in the United States and the United Kingdom. Nevertheless, many readers still view e-books as less readable than print books. The present study thus used combined EEG and eyetracking measures in order to test whether reading from digital media requires higher cognitive effort than reading conventional books. Young and eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 47 publications
11
81
0
2
Order By: Relevance
“…age generally resulted in lower scores in computer skills) or even negligible (such as the fact that women had slightly lower computer skills than men). As the age or gender distribution of knowledge in computers is not a static phenomenon but is a matter of dynamic change over time, the acceptance of tablet computers by patients-even the elderly-is most likely to improve significantly in the future [9,12]. Nevertheless, measures have to be undertaken to make this interaction more intuitive which is reflected by the rather large number of questions that arose during the electronic briefing concerning the interaction with the tablet computer.…”
Section: Discussionmentioning
confidence: 99%
“…age generally resulted in lower scores in computer skills) or even negligible (such as the fact that women had slightly lower computer skills than men). As the age or gender distribution of knowledge in computers is not a static phenomenon but is a matter of dynamic change over time, the acceptance of tablet computers by patients-even the elderly-is most likely to improve significantly in the future [9,12]. Nevertheless, measures have to be undertaken to make this interaction more intuitive which is reflected by the rather large number of questions that arose during the electronic briefing concerning the interaction with the tablet computer.…”
Section: Discussionmentioning
confidence: 99%
“…Students may be more likely to engage with and perceive as useful technologies with which they are already familiar; alternatively, they may have a strong preference for print-based texts based on prior experiences. A variety of factors are at play here: familiarity with and comfort levels of the medium or platform (Baek and Monaghan 2013;Chen et al 2014;Weisberg 2011), the cultural attitudes of learners (Kretzschmar et al 2013), the subject matter (John 2014), the length of text ( Students may declare their preference for print-based texts over e-texts, but they can also appreciate using a combination of the two (Dobler 2015;Falc 2013;Mizrachi 2015;Singer and Alexander 2016). While students overall appear to prefer printbooks, they are also satisfied with e-texts (Jeong 2012).…”
Section: The Importance Of Preference and Familiaritymentioning
confidence: 99%
“…Students reported best test scores when using their preferred medium, suggesting that preference affects their metacognitive processes. Interestingly, a study of reading effort on three different platforms (print, tablet and e-reader) showed that all participants preferred reading a print-based text, despite it not requiring more effort to read on a screen (Kretzschmar et al 2013). The authors suggested that this may be due to participants' cultural attitudes towards screen use.…”
Section: The Importance Of Preference and Familiaritymentioning
confidence: 99%
“…With a few exceptions (e.g., Benedetto et al, 2013), experiments are typically conducted with short texts where no page turning is needed. Alternatively, to ensure adequate experimental control, haptics is disabled by, e.g., the experimenter turning the pages on cues from the participant (Kretzschmar et al, 2013). Some interesting empirical evidence at a general level of haptics and empathy is also starting to emerge in the past year.…”
Section: Empathy and Digitizationmentioning
confidence: 99%